The effect of leader member exchange to dimension of readiness for change - Banguntopo, Unggul Satrio (Faculty of Economics and Business, Jenderal Soedirman University, 2018)
Organizational change has been a must for companies in preserving their sustainability. PT. Bank Rakyat Indonesia is one of state-owned companies which is now transforming massively both in its human resource sector and business process. The objective of this research is to explore deeper understanding about to what extent the influence of internal interaction between leader and member in organization structure towards employee’s readiness for change. The employee readiness for change itself are viewed from five perception employee’s personal dimensions; appropriateness of the change, need for change, personal valence, principal support and understanding of the change. The result using logistic regression test shows that leader-member interaction (LMX) has significance impact appropriateness of the change, need for change, and understanding of the change. The study can infer that, for organisation, the most important thing to create employee’s readiness for change is to provide adequate support “climate” from top-down to create readiness for change holistically.